(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In order to better understand how to cultivate transformational leadership in Indian firms, this study delves into the function of interpersonal competences. A unique set of people abilities is necessary for transformational leadership, which is defined by the capacity to inspire and encourage followers to accomplish outstanding results. The impact of transformational leaders’ abilities to establish teams, communicate effectively, resolve conflicts, and understand and manage emotions on their success in the Indian business world is the subject of this study. Managers at the mid- and upper levels of different businesses participated in the study through a mixed-methods strategy that included quantitative surveys and qualitative interviews. The results show that a leader’s capacity to connect with staff, cultivate a healthy company culture, and propel change is significantly improved by high levels of emotional intelligence. A compelling vision and team alignment can be articulated and maintained through effective communication. The ability to resolve conflicts and develop cohesive teams was also determined to be critical for keeping everyone on the same page during times of change. The research highlights the need for individualized leadership training programs that target these interpersonal skills. Executives can gain the knowledge and skills they need to succeed in the Indian business climate through these types of training. This study provides useful information for creating transformative leaders in India and adds to our knowledge of leadership dynamics in developing economies.